The Relationship of Food Fiscal Spending to Food Security in the Maluku Islands and Its Implications for the Free Nutritious Meal Program - Maryam Sangadji; Yusuf Wana Sanjaya; Fadhil Shafriandi Ramli; Ali Tutupoho (LP2M IAIN Palopo, 2026)
Food security is a fundamental issue in the development of archipelago regions that face limited access and distribution of food. This study analyzes the relationship between food fiscal spending and food security in Maluku Province and its implications for the Free Nutritious Meal Program (MBG). Data for the 2019–2024 period includes the realization of food spending by the central and regional governments as well as the Food Security Index (IKP) from eleven districts/cities in Maluku. The analysis was carried out descriptively and quantitatively using the Fixed Effect regression model in three regions with complete fiscal data (Ambon, Southeast Maluku, and Tual). The results show that food fiscal spending increased from IDR 58.30 billion (2019) to IDR 825.7 billion (2024) with an average growth of 9.99% per year, but the distribution is uneven and dominated by Ambon City. The average IKP increased from 57.69 (2019) to 63.26 (2023) and then decreased to 54.64 (2024). The data panel estimates showed a positive and significant relationship between fiscal expenditure and CPI (R² = 0.737; p < 0.01). The findings confirm that increasing public spending has not automatically strengthened food security without effective governance, spatial equity, and integration of MBG with local food systems